Does the dose make the poison? Neurotoxic insecticides impair predator orientation and reproduction even at low concentrations. Issue 4 (20th January 2022) - Passos, Luis C; Ricupero, Michele; Gugliuzzo, Antonio; Soares, Marianne A; Desneux, Nicolas; Carvalho, Geraldo A; Zappalà, Lucia; Biondi, Antonio
Abstract: BACKGROUND: Pesticides can be noxious to non‐target beneficial arthropods and their negative effects have been recently recognized even at low doses. The predator Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) plays an important role in controlling insect pests in solanaceous crops, but its concurrent herbivory often poses relevant concerns for tomato production. Although insecticide side effects on N. tenuis have been previously studied, little is known on the potential implications of neurotoxic chemicals at low concentrations. We assessed the baseline toxicity of three neurotoxic insecticides (lambda‐cyhalothrin, spinosad and chlorpyrifos) on N. tenuis by topical contact exposure. The behavioral and reproduction capacity of the predator was then investigated upon exposure to three estimated low‐lethal concentrations (LC1, LC10 and LC30 ). RESULTS: Predator survival varied among insecticides and concentrations, with LC30 /label rate ratios ranging from 8.45% to 65.40% for spinosad and lambda‐cyhalothrin, respectively. All insecticides reduced the fertility of N. tenuis females at all estimated low‐lethal concentrations. Chlorpyrifos seriously compromised predator orientation towards a host plant even at LC1, while the same effect was observed for lambda‐cyhalothrin and spinosad solely at LC30 . Lambda‐cyhalothrin (at all concentrations) and chlorpyrifos (at LC10 and LC30 ) also affected the time taken by N. tenuis females to make a choice. CONCLUSION: The results indicate that all three insecticides can be detrimental to N. tenuis and should be avoided when presence of the predator is desirable. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Neurotoxic insecticides negatively affected the behavior and reproduction of the predator Nesidiocoris tenuis, even at low concentrations. Our study suggest that these compounds should be avoided when the presence of the predator is desirable.